Married Men and Vasectomy: A Focused Group Study in an Urban Community in Ghana - Stella Appiah PhD, MPhil, RN; James Kwaku Agyen Bsc, MSc, MPhil; Isabella Garti MN, BSc, RM; Awube Menlah MN, BSc, RN (SAGE Publishing, 2018)
An effective method of birth control in men yet least accepted and patronized is vasectomy. Vasectomy provides health benefits to the user, his direct family, and the entire population as it helps to control population growth. This article explored the beliefs and attitudes of commercial drivers on vasectomy in an urban community in Ghana. The study employed qualitative exploratory design using focus group discussion. Data were collected from 12 married men between the ages of 45 to 60 years who were selected through purposive sampling method. The focus group discussions were audiotaped, handwritten, and recorded. Recorded data were then transcribed verbatim, and the current version of the NVivo software for analyzing qualitative data was used to manage the data. Three major themes emerged from the study: knowledge of respondents on vasectomy, beliefs, and attitudes of married men toward vasectomy. Each of the themes had three subthemes. The study revealed that vasectomy was perceived by some of the respondents to be synonymous to castration which comes with negative effects. Inadequate knowledge, negative perceptions, future uncertainty, and the irreversible nature of vasectomy emerged as contributing to the low patronage and some of the reasons why most of the respondents had no intentions of opting for vasectomy. In view of these findings, it is imperative for all stakeholders to give urgent attention to behavior change strategies that can be put in action to ameliorate the effects of these negative attitudes and misbeliefs. Ultimately, the tide can be turned around and vasectomy will be a preferred alternative when it comes to family planning in Ghana.